PERFORMANCE OF NATIONAL ORGANIZATION EMPLOYEE RELATIONS: LITERATURE REVIEW - Fahriski, Dimas; Zagladi, Arief Noviarakhman; Nora, Elfia (PT. Media Edutama Nusantara, 2025)
This study aims to analyze the relationship between organization performance and employee relations through a literature review approach. The methods used include collecting data from journals published in the last 10 years, from 2015 to 2025, from credible sources such as Google Scholar, DOAJ, Scopus, and drawing implicative conclusions. The results show that organizational performance, measured by objectives such as profitability, employee satisfaction, and innovation, is greatly influenced by harmonious employee relations through two-way communication, manager trust, and remote work adaptation. Specifically in national organizations such as state-owned enterprises and private companies in Indonesia, practices to minimize labor conflicts, increase productivity, and provide competitive advantages with practical implications require HRM strategies that focus on employee empowerment. The literature confirms a strong positive relationship between employee relations and organizational performance, where good employee relations drive individual productivity that reflects overall organizational performance, reduce labor conflicts, and provide competitive advantage through psychological empowerment.